2009
DOI: 10.1007/s11249-009-9467-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of T4 Heat Treatment on Tribological Behavior of Za27 Alloy Under Lubricated Sliding Condition

Abstract: The effects of heat treatment on the microstructure, hardness, tensile properties, and tribological behavior of ZA27 alloy were examined. The alloys were prepared by conventional melting and casting route. The heat treatment of samples included the heating up to 370°C for 3 or 5 h, quenching in water, and natural aging. Lubricated sliding wear test were conducted on as-cast and heat-treated ZA27 samples using block-on-disc machine. The friction and wear behavior of alloys were tested in contact with steel disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Furthermore, Prasad [13] reported that the presence of various phases with different thermal characteristics and mechanical properties in the structure of non-homogeneous as-cast alloys results in creation of residual stresses on a microscale. Based on this fact, Miroslav et al [2] concluded that obtained uniformity after heat treatment relieves the residual stresses and enhances the wear characteristics.…”
Section: Wear Test Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, Prasad [13] reported that the presence of various phases with different thermal characteristics and mechanical properties in the structure of non-homogeneous as-cast alloys results in creation of residual stresses on a microscale. Based on this fact, Miroslav et al [2] concluded that obtained uniformity after heat treatment relieves the residual stresses and enhances the wear characteristics.…”
Section: Wear Test Resultsmentioning
confidence: 97%
“…Some of the attractive properties of these alloys are lower density, excellent castability, good machinability, excellent corrosion resistance in a variety of environments and superior wear properties [1][2][3][4][5]. Desirable characteristics and low manufacturing cost of these alloys enable them to be considered as competing materials for cast metals such as high strength aluminum alloys, cast iron, copper alloys and brass.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations